Latent Adrenal Insufficiency: Concept, Clues to Detection, and Diagnosis - Yamamoto, Toshihide (Endocrine practice, 2018)
In 1855, Thomas Addison described an illness now known as Addison disease (AD) caused by damage to the adrenal cortex and manifesting in weakness, weight loss, hypotension, gastrointestinal disturbances, and brownish pigmentation of the skin and mucous membranes. Corticosteroid supplementation, corticotropin (adrenocorticotropic hormone [ACTH] of medicinal use) test, and anti-adrenal auto-antibodies (AA) have come into use in the 100 years since Addison's death. Following the methodological innovations, 4 disorders which share impaired response to corticotropin in common have been discovered (i.e., partial AD, apigmented adrenal insufficiency [AI], subclinical AI, and the AA-positive state exclusively in subjects proven to have an impaired response to corticotropin). As they are hidden, potentially serious conditions, these disorders are bound together as latent AI (LAI). Diagnosis of AD is often delayed, which may lead to adrenal crisis. If LAI were widely recognized, such delays would not exist and crises would be averted. The 3 existing guidelines do not refer much to LAI patients outside those in acute situations. To address this, information relevant to clinical manifestations and diagnostic tests of LAI was sought in the literature. Signs and symptoms that are useful clues to begin a diagnostic workup are presented for endocrinologists to identify patients with suspected LAI. The utility of 2 corticotropin test protocols is reviewed. To endorse LAI shown by the corticotropin test, monitoring items following corticosteroid supplementation are cited from the guidelines and supplemented with the author's observations. AA = anti-adrenal auto-antibodies; Ab = antibodies; ACA = AA detected by immunofluorescence; ACTH = adrenocorticotropic hormone; AD = Addison disease; AI = adrenal insufficiency; DHEA = dehydroepiandrosterone; GC = glucocorticoid; IFA = immunofluorescence assay; LAI = latent AI; LDT = low-dose test; MC = mineralocorticoid; 21OHAb = anti-21-hydroxylase Ab; ST = standard test; URI = upper respiratory infection.